α-Fe2O3 based nanomaterials as gas sensors - Mirzaei, A.; Hashemi, B.; Janghorban, K. (Journal of materials science. Materials in electronics, 2016)
Interest in detecting and determining concentrations of toxic and flammable gases has constantly been on the increase in recent years due to increase of modernization, industrialization and high standards of life. Detection of such gases is very important in many different fields such as industrial emission control, household and social security, vehicle emission control and environmental monitoring. Metal oxide gas sensors are among most important devices to detect a large variety of gases. α-Fe 2 O 3 , an environmental friendly semiconductor ( E g = 2.1 eV), is the most stable iron oxide under ambient atmosphere and because of its low cost, high stability, high resistance to corrosion, and its environmentally friendly properties is one of the most important metal oxides for gas sensing applications. This is the first review about gas sensing properties of α-Fe 2 O 3 nanostructures. In this paper gas sensing properties of α-Fe 2 O 3 are extensively reviewed. After a brief explanation about metal oxide gas sensors and α-Fe 2 O 3 , sensors based on α-Fe 2 O 3 nanomaterials have been reviewed. Gas sensing section is divided into five subsections: pure α-Fe 2 O 3 gas sensors, metal/α-Fe 2 O 3 gas sensors, metal oxide/α-Fe 2 O 3 gas sensors, polymer/α-Fe 2 O 3 gas sensors and graphene/α-Fe 2 O 3 gas sensors.